Ἁγιάζω antara Status dan Proses: Analisis Diskursif Ibrani 10:10 dan Surat-Surat Paulus - Pieter G.O. Sunkudon; Royke Lepa (Jurnal Salvation, 2026)
Abstract: This article examines the theological meaning of hagiazō (ἁγιάζω) in Hebrews 10:10 and the Pauline letters through a lexical analysis developed into a discourse-based theological reading of the Greek text. In contrast to approaches that treat sanctification as a systematic or monolithic concept, this study situates the term within the discursive function and theological purpose of each corpus. The analysis demonstrates that in Hebrews 10:10, hagiazō affirms sanctification as a definitive soteriological status grounded in Christ’s once-for-all sacrifice. In the Pauline letters, however, sanctification is articulated contextually and pastorally: as a new orientation of life in Romans, a holy identity shaping communal formation in Corinthians, and an ethical calling rooted in God’s will in Thessalonians. This comparison shows that the differences between Hebrews and Paul are complementary rather than contradictory. Sanctification is thus understood as God’s grace, definitively granted in Christ and dynamically actualised in the life of the believing community. Abstrak: Artikel ini mengkaji makna teologis ἁγιάζω (hagiazō) dalam Ibrani 10:10 dan surat-surat Paulus melalui analisis leksikal yang dikembangkan menjadi pembacaan teologis berbasis wacana teks Yunani. Berbeda dari pendekatan yang memperlakukan pengudusan secara sistematik atau monolitik, penelitian ini menempatkan istilah tersebut dalam fungsi diskursif dan tujuan teologis masing-masing korpus. Hasil analisis menunjukkan bahwa dalam Ibrani 10:10, ἁγιάζω menegaskan kekudusan sebagai status soteriologis yang final melalui korban Kristus yang dipersembahkan sekali untuk selama-lamanya. Sebaliknya, dalam surat-surat Paulus, pengudusan diartikulasikan secara kontekstual dan pastoral: sebagai arah hidup baru dalam Roma, identitas kudus dalam Korintus, dan panggilan etis dalam Tesalonika. Perbandingan ini memperlihatkan bahwa perbedaan tersebut bersifat komplementer, bukan kontradiktif. Pengudusan dipahami sebagai anugerah Allah yang telah dianugerahkan di dalam Kristus dan diaktualkan secara dinamis dalam kehidupan umat.